Assessing the Variability in the Relationship Between the Particulate Backscattering Coefficient and the Chlorophyll a Concentration From a Global Biogeochemical‐Argo Database. Issue 2 (15th February 2018) - Barbieux, Marie; Uitz, Julia; Bricaud, Annick; Organelli, Emanuele; Poteau, Antoine; Schmechtig, Catherine; Gentili, Bernard; Obolensky, Grigor; Leymarie, Edouard; Penkerc'h, Christophe; D'Ortenzio, Fabrizio; Claustre, Hervé
Abstract: Characterizing phytoplankton distribution and dynamics in the world's open oceans requires in situ observations over a broad range of space and time scales. In addition to temperature/salinity measurements, Biogeochemical‐Argo (BGC‐Argo) profiling floats are capable of autonomously observing at high‐frequency bio‐optical properties such as the chlorophyll fluorescence, a proxy of the chlorophyll a concentration (Chl a ), the particulate backscattering coefficient (bbp ), a proxy of the stock of particulate organic carbon, and the light available for photosynthesis. We analyzed an unprecedented BGC‐Argo database of more than 8, 500 multivariable profiles collected in various oceanic conditions, from subpolar waters to subtropical gyres. Our objective is to refine previously established Chl a versus bbp relationships and gain insights into the sources of vertical, seasonal, and regional variability in this relationship. Despite some regional, seasonal and vertical variations, a general covariation occurs at a global scale. We distinguish two main contrasted situations: (1) concomitant changes in Chl a and bbp that correspond to actual variations in phytoplankton biomass, e.g., in subpolar regimes; (2) a decoupling between the two variables attributed to photoacclimation or changes in the relative abundance of nonalgal particles, e.g., in subtropical regimes. The variability in the bbp :Chl a ratio in the surface layer appears to be essentially influenced by the type of particles and by photoacclimation processes. The large BGC‐Argo database helps identifying the spatial and temporal scales at which this ratio is predominantly driven by one or the other of these two factors. Key Points: The bbp ‐to‐Chl a relationship varies along the water column, as well as with seasons and oceanic regions The bbp ‐to‐Chl a ratio is a valuable biogeochemical proxy for assessing the nature of the particulate assemblage and revealing photoacclimation processes The BGC‐Argo float network yields an unprecedented amount of quality data for studying biogeochemical processes at a global scale and along the vertical dimension